The Influence of Self-concept on Career Maturity of Adolescent Members of Youth Organization in Kaliboyo Village - Taufik Siswanto Wiguno; Tritjahjo Danny Soesilo; Yustinus Windrawanto (Universitas Pendidikan Ganesha, 2020)
This study aimed to explore the influence of self-concept on career maturity of adolescent members of youth organization’s members in Kaliboyo village, Tulis sub-district, Batang Regency. The subjects of this study were 75 adolescent members of youth organization in Kaliboyo village, Tulis sub-district, Batang Regency taken by total sampling technique. The data collection technique used a closed-ended questionnaire model with a Likert scale. The data analysis technique in this study was conducted by simple linear regression. The result of the study showed a value of p=0.000 (p<0.05) which means there were positive and significant influences of self-concept on career maturity of adolescent members of youth organization’s members in Kaliboyo village, Tulis sub-district, Batang Regency in 2019. The result of the regression test showed that the contribution of self-concept on career maturity was 15.7%.